Senior officials from 15 African and asian countries on study mission to UPM innovation ecosystem - Universiti Putra Malaysia, Pejabat Strategi Korporat dan Komunikasi (Pejabat Strategi Korporat dan Komunikasi, Universiti Putra Malaysia, 2018)
SERDANG - World Intellectual Property Organization (WIPO), Geneva, together with Swedish Patent and Registration Office (PVR) and Swedish International Development Cooperation Agency (Sida), sponsored 21 senior officials from 15 Least Developed Countries (LDC’s) for a 1 week capacity building programme at Putra Science Park (PSP) in UPM to learn the successful innovation ecosystem model. The PSP has won several national awards and is recognised internationally as an excellent model for innovation.